Gold nanoparticle-DNA aptamer conjugate-assisted delivery of antimicrobial peptide effectively eliminates intracellular Salmonella enterica serovar Typhimurium. (October 2016) - Yeom, Ji-Hyun; Lee, Boeun; Kim, Daeyoung; Lee, Jong-kook; Kim, Suk; Bae, Jeehyeon; Park, Yoonkyung; Lee, Kangseok
Abstract: Antimicrobial peptides (AMPs) are a promising new class of antibacterial compounds. However, their applications in the treatment of intracellular pathogenic bacteria have been limited by their in vivo instability and low penetrating ability into mammalian cells. Here, we report that gold nanoparticles conjugated with DNA aptamer (AuNP-Apt) efficiently delivered AMPs into mammalian living systems with enhanced stability of the AMPs. C-terminally hexahistidine-tagged A3-APO (A3-APO His ) AMPs were loaded onto AuNPs conjugated with His-tag DNA aptamer (AuNP-Apt His ) by simple mixing and were delivered into Salmonella enterica serovar Typhimurium ( S. Typhimurium)-infected HeLa cells, resulting in the increased viability of host cells due to the elimination of intracellular S. Typhimurium cells. Furthermore, the intravenous injection of AuNP-Apt His loaded with A3-APO His into S. Typhimurium -infected mice resulted in a complete inhibition of S. Typhimurium colonization in the mice organs, leading to 100% survival of the mice. Therefore, AuNP-Apt His can serve as an innovative platform for AMP therapeutics to treat intracellular bacterial infections in mammals. Graphical abstract: Schematic diagram of the generation of His-tagged AMP loaded onto His-aptamer conjugated AuNP and the delivery of AMPs into S. Typhimurium -infected mammalian cells.